LANGUAGE, LAND, AND LEARNING: AGRARIA SPIRITUALITY AND ENVIRONMENT PEDAGOGY IN MAKASSAR MANTRAS - Supriadi, Supriadi; Kurniawan, Eri; Saifullah, Aceng Ruhendi; Akbar, Fadhly (ppjbsip, 2025)
This study explores the ecological, spiritual, and agrarian values embedded in the rice mantras of the Makassar community through an ecosemiotic lens. Employing a qualitative approach, data were drawn from traditional lontarak texts, field observations, and interviews with local farmers and traditional leaders. Analysis utilized the three-dimensional ecolinguistic model by Bang and Døør, biological, sociological, and ideological, alongside Barthes' semiotic theory to interpret signs and meanings within the mantra texts. Findings reveal that these mantras are more than ritual expressions; they serve as oral educational texts that encode agrarian knowledge, cosmological beliefs, and environmental ethics. For instance, expressions like “I will use it for good and enjoyment” convey ecological intent and socio-spiritual gratitude. Meanwhile, metaphors such as “my fortune is like a mountain” construct symbols of abundance tied to divine blessing. Moreover, references to cardinal directions emphasize a cosmic understanding of agriculture as an integrated relationship among humans, nature, and the divine. Viewed through the lens of educational discourse analysis, these mantras represent indigenous eco-pedagogy transmitting values, practical wisdom, and cosmological awareness across generations. The study calls for renewed recognition of local linguistic heritage as cultural artifacts and as sources of environmental education. Future studies are encouraged to explore how agrarian discourses can be integrated into formal and non-formal education to promote ecological literacy and sustainability ethics in rural and urban contexts